Enrichment of Mantle-derived Fluids in the Formation Process of Granitoids: Evidence from the Himalayan Granitoids around Kunjirap in the Western Qinghai-Tibet Plateau - Yaohui, JIANG; Hongfei, LING; Shaoyong, JIANG; Xunruo, ZHOU; Xingjian, RUI; Wanzhi, YANG (Acta geologica Sinica (Beijing), 2002)
Taking the Himalayan granitoids around Kunjirap in the western Qinghai-Tibet plateau as an example, the authors present in this paper the characteristics of the granitoids rich in mantle-derived fluid components and discuss their rock-forming mechanism. The research results indicate that the rock assemblage of the studied granitoids involves diopside syenite-diopside granite-biotite (monzonitic) granite, consisting mainly of K-feldspar, oligoclase, quartz, iron-phlogolite, diopside and edenite. The rocks are rich in mantle-derived fluid components of volatiles including F, alkali metal elements such as K, Na, Rb, Sr and Ba, and radiogenic heat-producing elements such as U and Th. They were generated by the influx of mantle-derived fluids into the lower crust to give rise to partial melting during the lithosphere thinning in the Qinghai-Tibet plateau.